Dialectical Indigenism and Cognitive-Evaluative Compassion in Rosario Castellanos's Balún Canán. - Anzzolin, Kevin M. (Confluencia: Revista Hispánica de Cultura y Literatura)
A literary criticism of the book “Balón Canán” by Rosario Castellanos is presented. Topics discussed include information on the narrating how family matters are affected by national politics; dialectical indigenism character of Rosario Castellanos’s work; and the information on the clarify the notion of dialectical indigenism by invoking Martha Nussbaum’s novel interpretation of compassion.